Effect of nitrogen on growth, yield and quality of fodder pearl millet (Pennisetum glaucum) cultivars under irrigated condition of North-Western Rajasthan - Meena, S.N.; Jain, K.K.; Prasad, Dasharath; Ram, Asha (Annals of Agricultural Research, 2014)
Effect of nitrogen on growth, yield and quality of fodder pearl millet (Pennisetum glaucum) cultivars under irrigated condition of North-Western Rajasthan.Results of the field experiment that Â "Rajasthan Bajra chari-2" cultivar of pearl milletsignificantly higher plant height, total numbers of tillers per plant, dry matter accumulation per plant, green and dry fodder yield, crude protein content and ether extract was recorded. However, "Pusa Bajra-266" recorded significantly higher total digestible nutrient, nitrogen free extract and crude fibre. Application of nitrogen up to 120 kg/ha significantly increased the plant height, dry matter accumulation, tillers per plant, green, and dry fodder yield, crude protein, and ether extract which was at par with 160 N kg/ ha. However, the crude fibre content, nitrogen free extract and total digestible nutrient were significantly decreased with application of 120 N kg/ha.